2003
DOI: 10.1007/s00216-003-1896-z
|View full text |Cite
|
Sign up to set email alerts
|

Analytical developments in toxicological investigation of drug-facilitated sexual assault

Abstract: This paper gives a general overview of the drug-facilitated sexual assault phenomenon. Sexual assault perpetrated on both women and men, while incapacitated by so-called date-rape drugs, recently became the focus of many investigations conducted by law enforcement agencies in the US throughout the 1990s; an alarming increase in reports of this crime as well as in the number of scientific publications on drug-facilitated sexual assault has been observed. The list of drugs reportedly associated with sexual assau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 40 publications
1
53
0
Order By: Relevance
“…One of the most important issues in DFSA investigations is the sensitivity of the screening and confirmatory techniques because some of the compounds (e.g., BZPs) are typically used in a single low dose (16,17 ). Kintz et al (18 ) demonstrated that the LC-MS and gas chromatography (GC)-negative chemical ionization-MS/MS techniques are the most sensitive for detecting low quantities of the drug metabolite 7-aminoflunitrazepam several days after administration of flunitrazepam.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important issues in DFSA investigations is the sensitivity of the screening and confirmatory techniques because some of the compounds (e.g., BZPs) are typically used in a single low dose (16,17 ). Kintz et al (18 ) demonstrated that the LC-MS and gas chromatography (GC)-negative chemical ionization-MS/MS techniques are the most sensitive for detecting low quantities of the drug metabolite 7-aminoflunitrazepam several days after administration of flunitrazepam.…”
Section: Discussionmentioning
confidence: 99%
“…Clonazepam (5-(2-chlorophenyl)-7-nitro-2,3-dihydro-1,4-benzodiazepin-2-one, i) has been identified as one of the more common benzodiazepines that has been used illegally [16,17] and has been reported in cases of sexual assault [18]. It is one of the more potent 1,4-benzodiazepines and is prescribed for the treatment of a wide range of afflictions such as sleep disturbance, depression [19], anxiety and panic disorders [20], forms of parasomnia [21], obsessive-compulsive disorder [22], seizures [23], certain types of migraines [24] and epilepsy [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 15 years GHB (and its related analogues such as gamma-butyrolactone (GBL)) has been linked to cases of drug-facilitated sexual assault (DFSA), more commonly termed "date-rape" (7)(8)(9)(10). In such cases toxicological proof of GHB administration is difficult due to its endogenous nature (0.2 -1 mg/L in urine), and rapid elimination from the body (half-life 20 -45 min), which results in a return to baseline concentrations in urine after only 8 hours post-administration (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%